2019
DOI: 10.3389/fnbeh.2019.00019
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hippocampal Sex Hormones Receptors in Modulation of Depressive-Like Behavior Following Chronic Anabolic Androgenic Steroids and Exercise Protocols in Rats

Abstract: The aim of this study was to evaluate alterations in depressive-like behaviors in rats following chronic administration of a supraphysiological dose of anabolic androgenic steroids (AASs) as well as exposure to a prolonged exercise protocol. The role of hippocampal sex hormones receptors in the modulation of depressive-like behavior was also assessed. A total of 48 male Wistar albino rats were divided into six groups: control, exercise (1 h/day, five consecutive days), nandrolone-decanoate (ND, 20 mg/kg/week, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Although there are various investigated brain regions responsible for mood regulation [32,33], the majority of studies in the field of behavioral alterations are focused on the hippocampus [34,35]. It is worth noticing that increased oxidative damage in all specific brain regions responsible for mood regulation correlates with mood disorders [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are various investigated brain regions responsible for mood regulation [32,33], the majority of studies in the field of behavioral alterations are focused on the hippocampus [34,35]. It is worth noticing that increased oxidative damage in all specific brain regions responsible for mood regulation correlates with mood disorders [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…There are studies showing beneficial, antiox-idant effects in the rat heart following testosterone administration in lower doses [16]. On the contrary, prooxidative effects of testosterone and its derivatives on CV [17], endocrine [18], and behavioral [19,20] properties were proven in our previous papers, dealing with the administration of supraphysiological doses in male rats. Investigations with similar protocols in female rodents have not been represented in literature so far, except androgen administration to female rats to mimic PCOS characteristics [13].…”
Section: Introductionmentioning
confidence: 99%
“…Androgen receptor (AR) may influence the development of major depressive disorder [ 58 ]. The study suggests that AR deficiency may accelerate the development of depression-like behavior in chronically mildly stressed mice [ 59 ]. The mechanism may be to regulate the expression of brain-derived neurotrophic factor (BDNF) by altering the expression of miR-204-5p [ 60 ], thereby affecting the depression-like behavior of CMS mice.…”
Section: Resultsmentioning
confidence: 99%
“…PPI network analysis showed that VEGFA, EGFR, CASP3, IL6, ESR1, and other targets have important implications in the treatment of depression with XPJYD. Studies have shown that AKT1, VEGFA, ESR1, IL6, and AR play an important role in the treatment of depression [ 47 49 , 53 , 55 , 59 , 60 ]. An experimental study showed that XPJYD reduced the serum and hippocampal levels of IL-6, TNF α, and other inflammatory factors in depression model rats and improved their learning and memory behaviors [ 66 ].…”
Section: Discussionmentioning
confidence: 99%